Stroke in the Middle-East and North Africa: A 2-year prospective observational study of stroke characteristics in the region—Results from the Safe Implementation of Treatments in Stroke (SITS)–Middle-East and North African (MENA). Issue 7 (October 2019) - Rukn, Suhail Al; Mazya, Michael V; Hentati, Faycal; Sassi, Samia Ben; Nabli, Fatma; Said, Zakharia; Faouzi, Belahsen; Hashim, Husnain; Abd-Allah, Foad; Mansouri, Benhan; Kesraoui, Selma; Gebeily, Souheil; et al.
Background and methods: Stroke incidence and mortality are reported to have increased in the Middle-East and North African (MENA) countries during the last decade. This was a prospective observational study to examine the baseline characteristics of stroke patients in the MENA region and to compare the MENA vs. the non-MENA stroke cohort in the Safe Implementation of Treatments in Stroke (SITS) International Registry. Results: Of the 13, 822 patients with ischemic and hemorrhagic stroke enrolled in the SITS-All Patients Protocol between June 2014 and May 2016, 5897 patients (43%) were recruited in MENA. The median onset-to-door time was 5 h (IQR: 2:20–13:00), National Institutes of Health Stroke Scale (NIHSS) score was 8 (4–13) and age was 65 years (56–76). Hypertension (66%) and diabetes (38%) were the prevailing risk factors; large artery stenosis > 50% (25.3%) and lacunar strokes (24.1%) were the most common ischemic stroke etiologies. In comparison, non-MENA countries displayed an onset-to-door time of 5:50 h (2:00–18:45), a median of NIHSS 6 (3–14), and a median age of 66 (56–76), with other large vessel disease and cardiac embolism as the main ischemic stroke etiologies. Hemorrhagic strokes (10%) were less common compared to non-MENA countries (13.9%). In MENA, only a low proportion of patients (21%) was admitted to stroke units. Conclusions: MENA patients are slightly younger, have a higher prevalence of diabetes and slightly more severe ischemic strokes, commonly of atherosclerotic or microvascular etiology. Admission into stroke units and long-term follow-up need to be improved. It is suspected that cardiac embolism and atrial fibrillation are currently underdiagnosed in MENA countries.